Experemental study of hydrogen peroxide/methane combustion - Muhamad Syukri, Shalihuddin (2010)
In this comparative study, a relationship of methane a traditional hydrocarbon fuel and hydrogen peroxide (H2O2) a combustion enhancer and oxidizer has been studied. Different concentrations of H2O2 were mixed for combustion and hazardous gases (COx) emissions. H2O2 was directly inserted into the burner by induction through the inlet manifold for dual fueling. 3L/m of methane diffused into 500ml of solutions which contained H2O2 at various volume percentages to form a mixture of methane/H2O2 used for the experiments to study the performance, combustion, and emissions characteristics. The flame became lean with full blue flame produced as the amount of oxygen produced increased through the functional groups obtain inside the blend which mainly formed by C-O stretching. Concentration graphs showed the amount of CO and unburned methane decreased while CO2 concentration increased Thus, this experimental study filled the objective of this study where is the addition of hydrogen peroxide can extend the lean operating limit, improve the lean burn ability and controlling the exhaust emission by reducing greenhouse gases.